Fair Inheritance Taxation in the Presence of Tax Planning - Matthias Wrede (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper analyzes to what extent tax planning impacts on the level of the inheritance tax rate perceived as fair. In a factorial survey conducted in Germany it finds out that tax planning increases the fair tax rate by roughly 4 percentage points. The fair tax rate is not only determined by the size of the bequest, the relationship of the heir to the bequeather, and the type of bequest, but also by the perceived intentions of the bequeather. The families with social motives should be taxed less than those without. The paper looks for support in optimum-tax theory. To this end, it develops a simple model that shows that taxation should not prevent individuals with warm-glow-of-giving motives to contribute substantially more to the social good than individuals without these motives.
Keywords: H24; H21; D64; 330